Prediction of Response to Androgen Deprivation Therapy and Castration Resistance in Primary Metastatic Prostate Cancer - (:unkn) unknown (KARGER, 2012)
Purpose: We tried to establish the predictive factors influencing the initial response, as well as its duration, and time to castration resistance (CR) for primary advanced prostate cancer (PC) with bone metastasis. Methods: We evaluated all patients initially receiving androgen deprivation therapy (ADT) for primary advanced PC with bone metastasis. A total of 982 patients with complete medical records available for analysis from 18 centers were included in this study. Age, initial PSA, Gleason score (GS) and extent of bone involvement (EBI) were recorded in a database. Results: Among all the patients, 896 (91.2%) responded to ADT initially. Pretreatment PSA and EBI were significant predictors in the multivariate model. Among the 659 patients who progressed into a CR state, the mean duration of response was 22.4 months. There was a significant correlation between the CR state and nadir PSA (nPSA) level and time to nPSA. Pretreatment PSA, EBI, GS, highest tumor volume in biopsy cores (%), number of positive biopsy cores, percent positive biopsy cores and time to nPSA were proven to be significant to predict a nPSA. Pretreatment PSA, GS and EBI were statistically significant predictors of PSA normalization in multivariate analysis. The limitation of the study depends on the retrospective design and a model was developed for low standardization as a result of using multicenter data. The patients enrolled in this study were from a relatively long period of time (1989-2008). Conclusions: The results of this study indicate that it is possible to predict the initial response to ADT by pretreatment PSA levels and EBI, while the duration of response can be reflected by a multitude of clinical factors including nPSA, TTnPSA, percent positive cores, biopsy GS and EBI. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Prostate cancer; Bone metastasis; Androgen deprivation therapy; Duration of response; Nadir PSA; Time to nadir PSA; Castration resistance; FUTURE-PROSPECTS; ANTIGEN; SURVIVAL; MANAGEMENT